Crystal structure of 4,8-di-tert-butyl-6,6-dichloro-13-ethyl-2,10-dimethyl-13,14-dihydro-12H-dibenzo[d,i][1,3,7,2]dioxazasilecine toluene 0.25-solvate - Kuchuk, Ekaterina A. (Acta Crystallogr E Crystallogr Commun, 2015)
The coordination polyhedron at the silicon atom in the title compound, C(26)H(37)Cl(2)NO(2)Si·0.25C(7)H(8), is typical for pentacoordinated silicon derivatives and represents a slightly distorted trigonal bipyramid with an N atom and a Cl atom in the apical positions and the two O atoms and the other Cl atom occupying the equatorial sites. There are two independent molecules in the asymmetric unit. The N–Si–Cl fragment in each is close to linear [178.24 (5) and 178.71 (5)°], in good agreement with 4e–3c theory, as is the elongation of the apical bond lengths [Si—Cl = 2.1663 (7) and 2.1797 (7) Å] in comparison with the equatorial bonds [Si—Cl = 2.0784 (7) and 2.0748 (7) Å]. Orthogonal least-squares fitting of the two independent molecules resulted in r.m.s. deviation of 0.017 Å. The conformations of the two molecules are almost the same, with corresponding torsion angles differing by less than 5.5°. The toluene solvent molecule is disordered about an inversion centre.